Leading on the edge: The nature of paramedic leadership at the front line of care. Issue 1 (January 2018) - Mercer, Danielle; Haddon, Arlene; Loughlin, Catherine
Abstract : Background: Health care organizations are considered complex systems that represent both formal leadership as well as more informal and shared leadership models. Implementing these models is essential for optimizing care and patient outcomes. The paramedic profession specifically, although considered informally, leads out of hospital patient care. Purpose: To date, few empirical studies investigate shared leadership in health care settings. In paramedicine specifically, studies of leadership are scarce, despite paramedics' essential role in leading on the front lines of care. Using an exemplar of paramedics, we examine what it means to informally lead on the front lines of patient care with the emphasis on paramedics responding out of hospital. Methodology: We employed a qualitative, semistructured interview methodology with 29 paramedics from a group of companies in central/eastern Canada to explore the conditions and practices surrounding shared leadership. Findings: Paramedics argue that, despite their job title, they classify themselves as informal leaders who share the leadership role. More specifically, the paramedics discuss the precursors, practices, and structural conditions surrounding shared leadership within the realm of emergency medical services. They note that they often face out-of-hospital care without a formal manager, requiring them to collectively lead. The leader will shift in times of urgency, and this is contingent on their skills and competence. Furthermore, managers routinely called upon paramedics to lead in their absence. Practice Implications: It is shown here that, although informally enacted, paramedics view leadership as a necessary competency for clinical practice. We argue that leadership development of paramedics must begin during their formal education and training as part of the core curriculum. As well, direct managers can promote an environment of shared leadership and encourage paramedics to practice leadership with quality of patient service in mind.